Culinary tourism and rural development: exploring the dynamic of “the Greek Breakfast” initiative in Santorini - Skordili, Sophia; Tsakopoulou, Konstantina (The Greek Review of Social Research, 2019)
During the last decade or so, culinary or food tourism has gained a prominent place in "special interest tourism" literature. It is widely believed that the (re)connection of tourist rural areas with their local agrifood base can contribute to sustainable and secure development away from the malfunctions of the prevalent mass tourism model. The paper explores the actual and potential interface between tourism and the local agrifood sector in Santorini, a small Mediterranean island and a major tourist destination, by examining the challenges and opportunities from the implementation of the "Greek Breakfast" initiative. The results of fieldwork research have revealed several impediments that hinder the project. Among other challenges, the absence of a coherent network of collaboration and communication among various stakeholders and the weak recognition of the benefits of food tourism by several local actors seem to be the more crucial ones.